Decrease of the Residual Strength During Creep - Madej, J. (Engineering Transactions, 1994)
In the article safety factors of the material under instantaneous and rheological static loadings have been described utilizing the idea of a damage parameter. Two safety factors have been introduced: the instantaneous factor related to the load level (named stress safety factor), and the time-dependent one, connected with the lifetime (named time safety factor). Damage development process under rheological conditions causes decrease of the rupture strength and implies an interrelation of these two safety factors. This relation has been analyzed for uniaxial as well as biaxial stress conditions, by constructing curves of constant safety in the meaning of the factors mentioned.